Mussel Fish (Polymesoda Erosa) and Microplastics inTallo River, Makassar, Indonesia - Yuliati; Anwar Daud; Anwar Mallongi; Burhanuddin Bahar; Hidayat (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Microplastics are plastic particles whose diameter is less than 5 mm, which can be a problem for the environment and public health. This study aimed to determine the Mussel Shellfish’s microplastic content (Polymesodaerosa) in the Tallo Makassar River. Methods: This type of research is observational with a laboratory approach using Minitab 16 software to determine the microplastic content of Mussel Shellfish(Polymesoda erosa) in the Tallo Makassar River. Results: The results of this study indicated that the abundance of microplastics in the Mussel Shellfish (Polymesodaerosa) at station 1 was 3.8 Mps/Ind, while at station II and station III was 0.8 Mps/Ind. For contaminants, station 1 was 80%, station II was 60%, and station III was 40%. The most types of microplastics were line and fragment types, while the most common microplastics found were blue, red and transparent. Conclutions: Mussel Shellfish (Polymesodaerosa) originating from the Tallo Makassar River contain microplastics. The highest abundance of microplastics was at station I of 3.8 Mps/Ind, while stations II and III were at 0.8 MPs/Ind. Station I is 80% for contaminants, Station II is 60%, and Station III is 40%.